2019
DOI: 10.1101/lm.050161.119
|View full text |Cite
|
Sign up to set email alerts
|

Reminders reinstate context-specificity to generalized remote memories in rats: relation to activity in the hippocampus and aCC

Abstract: Conditioned fear memories that are context-specific shortly after conditioning generalize over time. We exposed rats to a context reminder 30 d after conditioning, which served to reinstate context-specificity, and investigated how this reminder alters retrieval-induced activity in the hippocampus and anterior cingulate cortex (aCC) relative to a no reminder condition. c-Fos expression in dorsal CA1 was observed following retrieval in the original context, but not in a novel context, whether or not the memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 31 publications
5
21
1
Order By: Relevance
“…Also using MEG, Hebscher et al (2020) observed that inhibiting the precuneus with TMS led to slowed frontally-distributed activity early during the construction phase of autobiographical retrieval, consistent with disruption of frontally-mediated access to personal memories. These findings are also consistent with observations by Sekeres et al (2020) in their reminder experiment (see above), though the temporal precision was much lower in that study.…”
Section: Co-existence Of Mpfc and Hippocampally Mediated Representations Of Recent And Remote Memories And Their Interactionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also using MEG, Hebscher et al (2020) observed that inhibiting the precuneus with TMS led to slowed frontally-distributed activity early during the construction phase of autobiographical retrieval, consistent with disruption of frontally-mediated access to personal memories. These findings are also consistent with observations by Sekeres et al (2020) in their reminder experiment (see above), though the temporal precision was much lower in that study.…”
Section: Co-existence Of Mpfc and Hippocampally Mediated Representations Of Recent And Remote Memories And Their Interactionsupporting
confidence: 93%
“…The close correspondence between rodent and human studies on systems consolidation is illustrated nicely by Sekeres et al (2018bSekeres et al ( , 2020 who conducted homologous, functional neuroimaging studies on humans and IEG studies on rodents (see above). Using fMRI during encoding and retrieval of memories of the video clips from St-Laurent et al ( 2009), Sekeres et al (2018b) tracked memory transformation and its neural correlates over time in neurologicallyintact people.…”
Section: Time and Experience Dependent Changes In Memory Representations Mediated By The Hippocampus And Mpfc: Univarite Fmri Analysesmentioning
confidence: 82%
See 1 more Smart Citation
“…In previous reviews, we have noted a strong correspondence between human studies on memory consolidation and transformation and rodent studies conducted at the same level of analyses (Winocur et al, 2010;Dudai, 2012;Kandel et al, 2014;Sekeres et al, 2018aSekeres et al, , 2018bSekeres et al, , 2019. Here, we briefly review such findings in light of the different types of representations: detailed versus gist event-specific memory (Figure 1A), schematic event-general knowledge (Figure 1B), and what might be considered an animal analog to human abstract (semantic) knowledge (Figure 1C).…”
Section: A Note On Studies In Non-human Animals On Memory Consolidation and Transformationmentioning
confidence: 87%
“…Sekeres et al , 2018). Should task demands tax the memory system to retrieve such detail, we predict the hippocampus would be required – as demonstrated in rodent (and human) studies of memory in the absence of a learned schema (Winocur, Moscovitch and Bontempi, 2010; Sekeres et al , 2018, 2020; Sekeres, Winocur and Moscovitch, 2018).…”
Section: Discussionmentioning
confidence: 98%